Study of antibiotic resistance profiling of Staphylococcus aureus isolated from clinical specimens of the patients attending a tertiary teaching hospital from Chhattisgarh - Wankhade, Archana Bhimrao; Panda, Sanjibkumar; Hathiwala, Riddhi; Keche, Yogendra (International Journal of Research in Medical Sciences, 2017)
Background: Staphylococcus aureus is a pathogen causing wide spectrum of infections. It has tendency for the development of multidrug resistance thereby exposing the selection of appropriate treatment. Therefore, the present study was undertaken to find out the antibiotic susceptibility pattern of Staphylococcus aureus isolated from various clinical samples in teaching tertiary hospital. Methods: Total 85 Staphylococcus aureus was isolated from clinical samples (pus, urine, sputum and blood) tested. Identification of Staphylococcus aureus was done by standard conventional microbiological methods. Antibiotic susceptibility testing was done by using disk diffusion method as per CLSI guidelines. Results: Staphylococcus aureus was isolated maximum from pus samples followed by urine samples. Antibiotic susceptibility testing showed highest resistance against Penicillin (69%) and Erythromycin (51%) followed by Cotrimoxazole (50%) & Nitrofurantoin (50%). All the strains were sensitive to Vancomycin. Amongst the urine isolates all were sensitive to Norfloxacin. These percentages of sensitivities are characteristically higher in our study than the previous studies in the literature. In addition, out of 85 Staphylococcus aureus isolates, 26 isolates showed sensitivity to all antibiotics. Conclusions: From the present study we conclude that though the Staphylococcus aureus is usually having multidrug resistance pattern. So regular antimicrobial susceptibility surveillance is essential for area‐wise monitoring of the resistance patterns. This will be beneficial to preserve the effectiveness of antibiotics and for better patient management.